Diﬀerences between cardiorespiratory ﬁtness in adult men with asymptomatic or mild SARS-COV-2 infections - Sri Ramania, Nia; Apriantono, Tommy; Winata, Bagus; Syafriani, Rini; Bahri, Samsul; Iwo, Maria Immaculata; Budi Nugraha, Ashari (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. This study aimed to measure and compare CRF levels between COVID-19-infected adults with asymptomatic and mild symptoms.Methods. The participants in this study included 50 adult men, who were further divided into 2 equal categories: mild symp-tomatic (MS) and asymptomatic (AS) groups. These participants received a series of anthropometry and Rockport 1.5-mile run tests. During the Rockport 1.5-mile run test, their heart rate (HR) was continuously monitored using a Polar V800 GPS. Following this test, Borg’s CR10-scale rating of perceived exertion (RPE) was employed.Results. One-way ANOVA statistical test results showed a signiﬁcant diﬀerence (p = 0.007, ES = 0.140) between the MS and AS groups, where the VO2max in the AS group, was greater than the MS group (35.7 ± 7.1 vs 29.6 ± 8.4 ml/kg/min).Conclusions. Asymptomatic patients had a higher VO2max level than mildly symptomatic patients. Therefore, moderate-inten-sity exercise was recommended to increase CRF, thereby enhancing immunity and reducing the risk of contracting COVID-19.
Keywords: cardiovascular system cardiology; respiratory system pulmonology; sport physiotherapy